Skandinaviska filmer i världen. Om utlandssekvensers betydelse i Niels Arden Oplevs "Män som hatar kvinnor" (2009), Susanne Biers "Hævnen" (2010) och Sara Johnsens "Upperdog" (2009) - Marklund, Anders (Versita, 2012)
This article analyses three recent and very successful Scandinavian films – Niels Arden Oplev’s Män som hatar kvinnor/The Girl with the Dragon Tatoo (Sweden), Susanne Bier’s Hævnen/In a Better World (Denmark) and Sara Johnsen’s Upperdog (Norway) – in order to understand how the relationship between the national and the international is articulated. Focus is on the scenes taking place abroad and on the functions that these scenes fill within the films’ overall story and thematic concerns. One conclusion is that scenes set abroad allow the films to divert attention away from otherwise harsh representations of national communities. A brief concluding discussion suggests that such a use of the scenes may facilitate the films’ transnational distribution.
Scandinavian Films Abroad: Functions of Sequences Set in Foreign Countries in Niels Arden Oplevs "Män som hatar kvinnor" (2009), Susanne Biers "Hævnen" (2010) och Sara Johnsens "Upperdog" (2009)
Keywords: Nationell film; Transnationell film; Nostalgi; Resor; Utlandet; Niels Arden Oplev; Sara Johnsen; Susanne Bier; National cinema; Transnational cinema; Nostalgia; Travel; Foreign countries